Chemosaturation for primary and secondary liver malignancies: A comprehensive update of current evidence. (February 2023) - Vogel, Arndt; Ochsenreither, Sebastian; Zager, Jonathan S.; Wacker, Frank; Saborowski, Anna
Highlights: Locoregional therapies are useful therapeutic options for cancer patients with liver-limited disease. Chemosaturation with percutaneous hepatic perfusion allows the delivery of cytotoxic agents to the liver via the hepatic artery. Potential candidates for CS-PHP are patients with primary liver cancers, i.e. HCC and iCCA or patients with extrahepatic malignancies and liver-limited metastatic disease, most notably uveal melanoma. Phase-III data support the use of CS-PHP for patients with hepatic metastases from uveal melanoma. Abstract: Regional therapies for primary and secondary liver tumors have garnered interest in recent years and several types of treatment approaches have been pursued to control disease, palliate symptoms, and extend survival. Chemosaturation is an innovative way to deliver high-dose chemotherapy to the liver via the hepatic artery. Within the last decade, "isolated hepatic perfusion" (IHP) has evolved from an open surgical approach to a minimally invasive procedure, now termed "chemosaturation" (CS) with "percutaneous hepatic perfusion (PHP)". The most conclusive data on CS-PHP is currently available for patients with hepatic metastases from uveal melanoma (UM) - a rare but devastating disease with a poor long-term survival rate. A global phase-3 study and several cohort studies have provided compelling evidence that CS-PHP is an effective salvage treatment for liver-dominant metastatic UM in institutions with appropriate expertise. In this review we provide an overview on the technique, available clinical data, including safety and efficacy, and potential indications for CS-PHP.